New arylsparteine derivatives as positive inotropic drugs - Vito Boido; Marcella Ercoli; Michele Tonelli; Federica Novelli; Bruno Tasso; Fabio Sparatore; Elena Cichero; Paola Fossa; Paola Dorigo; Guglielmina Froldi (Taylor & Francis Group, 2017)
Positive inotropic agents are fundamental in the treatment of heart failure; however, their arrhythmogenic liability and the increased myocardial oxygen demand strongly limit their therapeutic utility. Pursuing our study on cardiovascular activities of lupin alkaloid derivatives, several 2-(4-substituted-phenyl)-2-dehydrosparteines and 2-(4-substituted-phenyl)sparteines were prepared and tested for inotropic and chronotropic activities on isolated guinea pig atria. Four compounds (6b, 6e, 7b, and 7f) exhibited significant inotropism that, at the higher concentrations, was followed by negative inotropism or toxicity. Compound 7e (2-(4-tolyl)sparteine) exhibited a steep dose-depending inotropic activity up to the highest concentration tested (300 µM) with an Emax of 116.5 ± 3.4% of basal force, proving less potent but much more active in comparison to the highest concentrations tested of digoxin and milrinone having Emax of 87.5 ± 3.1% and 52.2 ± 1.1%, respectively. Finally, docking studies suggested that the relevant sparteine derivatives could target the sigma-1 receptor, whose involvement in cardiac activity is well documented.